A Study of Simulation and Modeling of Three-Phase Electric Transformers - Shneen, Salam Waley; Oleiwi, Fadhil Mahmood; Dahloos, Jaber. O. (Journal of Fuzzy Systems and Control, 2025)
Under the title “A Survey of Simulation and Modeling of a Three-Phase Electric Transformer,” the present work presents a proposed modeling and simulation process for two types of step-up and step-down transformers. To design and build the model, a suitable transformer specification must be established through mathematical representation. To conduct tests using MATLAB, the proposed tests are conducted for both step-up and step-down cases by varying the number of turns in the primary and secondary windings to a step-up ratio of up to ten times, from 300 V to 3000 V, and step-down to 150 V. Transformer considerations for both step-up and step-down cases include maintaining the number of turns in the primary winding at 100 turns, while for step-up, we use the number of turns in the secondary winding at 1000 turns, to obtain ten times the input voltage at the transformer output. In the second test case, the input voltage is 300 V, and the primary coil has 100 turns. Changing the secondary coil from 1,000 turns to 50 turns halves the transformer's input voltage, resulting in a voltage of 50 V. A set of tests can be tabulated to represent different cases suitable for multiple transformers that can be built for the same prototype, as well as to serve as a reference for future studies.